Calibrating a fiber–matrix interface failure model to single fiber push-out tests and numerical simulations. (November 2021) - Rohrmüller, Benedikt; Gumbsch, Peter; Hohe, Jörg
Abstract: To characterize the fiber–matrix interface of a glass-fiber reinforced sheet molding compound (SMC), single-fiber push-out tests are performed and simulated numerically. The parameters of a cohesive zone model for the interface are calibrated on the single-fiber push-out tests. The fracture-toughness/energy release rate therein is determined from cyclic (loading–unloading) experiments. The matrix model, consisting of the nonlinear-elastic Neo-Hooke law with a Prony series to model viscoelastic behavior, is calibrated with data from nanoindentation tests by adjusting simulation curves to their experimental counterparts. Using the calibrated model of the single-fiber push-out, the influence of neighboring fibers and thermally induced residual stresses is shown. The interface damage initiates in the single-fiber push-out test at the indented fiber at positions closest to other fibers under the surface. In addition this is the position where the radially largest fiber expansion due to the Poisson effect is found. The results reveal that although the push-out test is simple to perform, the interpretation of its results might be a complicated task. Graphical abstract: Highlights: Single-fiber push-out tests on glass fiber reinforced sheet molding compound. Push-out simulation to characterize interface. Interface damage initiation at position of largest radial expansion of fiber. Influence of thermally induced residual stresses on push-out simulation. Nanoindentation experiment and simulation to characterize polymer matrix material.